Overview of the 2007 and 2008 campaigns conducted as part of the Greenland Summit Halogen-HO x Experiment (GSHOX) - Thomas, Jennie L.; Dibb, Jack E.; Stutz, J.; Von Glasow, Roland; Brooks, Steve; Huey, L. Gregory; Lefer, B. (Atmospheric Chemistry and Physics, 2012)
International audience From 10 May through 17 June 2007 and 6 June through 9 July 2008 intensive sampling campaigns at Summit, Greenland confirmed that active bromine chemistry is occurring in and above the snow pack at the highest part of the Greenland ice sheet (72°36' N, 38°25' W and 3.2 km above sea level). Direct measurements found BrO and soluble gas phase Br − mixing ratios in the low pptv range on many days (maxima < 10 pptv). Conversion of up to 200 pg m −3 of gaseous elemental mercury (GEM) to reactive gaseous mercury (RGM) and enhanced OH relative to HO 2 plus RO 2 confirm that active bromine chemistry is impacting chemical cycles even at such low abundances of reactive bromine species. However, it does not appear that Bry chemistry can fully account for observed perturbations to HO x partitioning, suggesting unknown additional chemical processes may be important in this unique environment, or that our understanding of coupled NO x -HO x -Br y chemistry above sunlit polar snow is incomplete. Rapid transport from the north Atlantic marine boundary layer occasionally caused enhanced BrO at Summit (just two such events observed during the 12 weeks of sampling over the two seasons). In general observed reactive bromine was linked to activation of bromide (Br − ) in, and release of reactive bromine from, the snowpack. A coupled snow-atmosphere model simulated observed NO and BrO at Summit during a three day interval when winds were weak. The source of Br − in surface and near surface snow at Summit is not entirely clear, but concentrations were observed to increase when stronger vertical mixing brought free tropospheric air to the surface. Reactive Bry mixing ratios above the snow often increased in the day or two following increases in snow concentration, but this response was not consistent. On seasonal time scales concentrations of Br − in snow and reactive bromine in the air were directly related.